Pengaruh Jumlah Penduduk Terhadap Pertumbuhan Ekonomi Provinsi Jambi Tahun 2016-2020 - Kasiyati Yunita Wulansari; Budi Darma (CITRA EKONOMI, 2021)
This study discusses the effect of population on the economic growth of Jambi Province in 2016-2020. The population variable is the independent variable, and the economic growth variable is the dependent variable. Residents have a role in various economic activities. Not only on the production side, the population also affects the level of consumption of an item which can have an impact on the economic growth of a region. To determine the effect of population on the economic growth of Jambi Province in 2016-2020, a simple linear regression analysis tool was used with the application of the t test with the aim of knowing whether the population variable had a partial or no effect on the variable economic growth. After the data is processed and analyzed, it can be concluded that based on the results of the t-test, the population variable has a partial (partial) influence on economic growth. From the magnitude of the coefficient of determination, the Adjusted R Square value is 0.657. This means that the population affects economic growth by 65.7%. While 24.3% is influenced by other variables that are not discussed in this study.